Changes and Fluctuations in Issue Ownership: The Case of Sweden, 1979–2010. (5th December 2014) - Christensen, Love; Dahlberg, Stefan; Martinsson, Johan
<x xml:space="preserve">Abstract</x> Issue ownership (IO) has been an important concept in the analysis of party behaviour, party strategy and party competition for several decades. More recently, it has also been of growing interest for research on voting behaviour. Traditionally, IO has been regarded as a stable phenomenon where parties have different issue profiles and are advantaged by different political issues or issue‐areas. Recently, however, many studies have reported change and fluctuations of IO, and the same studies also makes it clear that we know surprisingly little about what might cause, or facilitate, change in issue ownership. In fact, we do not even have systematic studies of how stable issue ownership is, or how frequent shifts in issue ownership actually are. The aim of this article is to explore the extent of change and stability in issue ownership in Sweden. For this purpose, the Swedish national election studies from 1979 to 2010 are utilised. Although recent research has indicated that changes in IO have increased over time, this is not supported in the Swedish case. Instead, issue ownership seems never to have been a particularly stable phenomenon. However, in line with our theoretical expectations, we show that ownership of economic issues is more volatile compared to ownership of other issues.